2018
DOI: 10.1371/journal.pone.0196721
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal and maternal serum creatinine levels during the early postnatal period in preterm and term infants

Abstract: We investigated the relationship of neonatal and maternal serum creatinine (nSCr and mSCr, respectively) with various maternal/infant characteristics at different gestational ages (GA). We reviewed medical records of neonates admitted to NICU. We collected data on birth weight, GA, Apgar scores, medications, etc. Spearman’s test was used to analyze the correlation between serum creatinine and continuous variables, and the Mann-Whitney U and Kruskal-Wallis tests for continuous variables between groups. The chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 27 publications
6
16
0
1
Order By: Relevance
“…Similar to the findings by Go et al [4], we observed a positive correlation of S cr at birth with GA (week, in the absence of data on days) in a large, pooled, and heterogeneous cohort (882 S cr observations, GA range 23–42 weeks) of neonates [4, 6, 7]. Although statistically significant, the clinical impact of this positive correlation is rather limited (24–40 weeks, 54.5–60.2 μmol/L, +10%).…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Similar to the findings by Go et al [4], we observed a positive correlation of S cr at birth with GA (week, in the absence of data on days) in a large, pooled, and heterogeneous cohort (882 S cr observations, GA range 23–42 weeks) of neonates [4, 6, 7]. Although statistically significant, the clinical impact of this positive correlation is rather limited (24–40 weeks, 54.5–60.2 μmol/L, +10%).…”
Section: Resultssupporting
confidence: 92%
“…Using an enzymatic assay for S cr measurement, Go et al [4] reported that the aforementioned fetal/maternal ratio increases with GA ( r = 0.71). The median neonatal S cr values were higher than maternal values from 29 weeks GA onward due to differences in trend patterns in neonatal (increase with advancing GA) and the stable median maternal S cr throughout the gestation [4, 5]. Using a systematic search and pooled analysis, Wiles et al [5] recently reported on maternal mean S cr reference values throughout pregnancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ELBW neonates who are born in the third trimester (> 28 weeks) were characterized by higher Crea birth Scr (median (95% CI); 0.79 mg/dl (0.50–1.29) at 32 weeks GA). This trend is also, albeit to a lesser extent, reflected by the maternal creatinine concentrations, which are generally, but marginally lower during the second trimester (0.59 mg/dl) as compared with the third trimester (0.61 mg/dl) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study also showed a moderate positive correlation of GFR with gestational age and anthropometric parameters. Whereas studies with inulin [33] and serum creatinine [34] demonstrated the correlation between gestational age and GFR, most studies done using Cystatin C have reported contrary findings [35,36]. This finding also suggested the need to considered a new formula for estimate GFR in the newborns that will incorporate anthropometric indices.…”
Section: Discussionmentioning
confidence: 99%